Role of Turbulent Transport in the Evolution of the ? Distribution Functions in the Plasma Sheet - Stepanova, M (Blackwell Publishing Ltd, 2015)
We studied the evolution of ion and electron distribution functions, approximated by κ distributions, in the plasma sheet with the distance from the Earth using the data of the Time History of Events and Macroscale Interactions during Substorms spacecraft mission. Five events were used to calculate the main parameters of the κ distribution. For these events at least four spacecraft were aligned along the tail between approximately 7 and 30-RE. It was found that for the majority of events the values of κ increase tailward. The observed radial profiles could be related to the inner magnetosphere sources of particle acceleration and to the net tailward transport of particles. This net transport is the result of a balance between the average regular bulk transport toward the Earth and the turbulent transport by eddies in the tailward direction. Key Points The index kappa distribution in the plasma sheet increases tailward Younger distributions are observed closer to the Earth Existence of turbulent transport explains this phenomenon ©2015. American Geophysical Union. All Rights Reserved.